Faktor Yang Berpengaruh Dalam Penggunaan Sistem INA CBGs Di Rumah Sakit Islam Jakarta Pondok Kopi - Putra, Daniel; Kirani, Niken; Rumana, Nanda Aula; Dewi, Deasy Rosmala (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
The implementation of the financing system in hospitals using the INA-CBGs system. The INA-CBGs system is a payment made at a package rate covering all components of resources in hospitals used in services, both medical and non-medical services. This research aims to identify the application of the INA-CBGs system and factors influencing the 6M method. The method used in this research is descriptive analysis with a qualitative approach. Descriptive analysis is the process of analyzing, explaining and summarizing events and phenomena from data obtained through interviews and field observations directly regarding the use of the INA-CBGs system. The results showed that the influence factor in the use of the INA-CBGs system can be reviewed from 6M. Man, the influence of humans is the incompatibility of the required crew with officers who do three jobs at once, the incompatibility of the educational background of outpatient coding officers with professional standards and the lack of implementation of special training regarding the INA-CBGs system. Materials, the influence of this factor is the unavailability of ICD-10 and ICD-9-CM books in casemix. Machines, the influence of machine factors, namely sometimes the internet is less stable and the lack of printer machines provided. Methods, the influence of the method factor, namely the unformed SPO from the hospital regarding the use of the INA-CBGs system. Money, the supporting factor is that there is a reward in overtime to encourage officers, while the obstacle is the difference in hospital costs and INA-CBGs packages. Market, supporting influence in the target market, namely inpatient BPJS patients with class 3 selection.